IMPROVEMENT OF ACCOUNTING OF PRODUCTION EXPENSES IN ENTITIES - Omanov Sanjar Kurbonazar ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article examines the issues of improving the accounting of production costs in economic entities in the example of grain processing enterprises. As a result of the research, proposals were developed for improving the production costs of grain processing enterprises based on product assortments.